ROLE OF PRODUCT SALES AT INDUSTRIAL PROMOTION: AN APPLIED STUDY IN IRAQI STATE COMPANY FOR MARKETING DRUG AND MEDICAL APPLIANCES (World Bulletin of Management and Law, 2023)
The research aims to improve the marketing capabilities of the executives in the industrial companies by helping them control the industrial promotion, which may bring their companies great profits. The research was applied in an Iraqi public company with an intentional sample of (71) managers. Through the questionnaire and statistical analysis, a group of results were reached, the most prominent of which is that product sales have a strong direct correlation with industrial promotion, and that the company should pay attention to indicator of sales activities so that it can raise industrial promotion levels.
Keywords: Product Sales; Industrial Promotion; Sales Efficiency; Sales Activities